Appendicitis Caused by Primary Varicella Zoster Virus Infection in a Child with DiGeorge Syndrome - Lotte Møller Smedegaard; Claus Bohn Christiansen; Linea Cecilie Melchior; Anja Poulsen (Hindawi Limited, 2017)
Introduction. Chickenpox is caused by varicella zoster virus (VZV). Although predominantly a mild disease, it can cause considerable morbidity and in rare occasions even mortality in healthy children as well as increased morbidity and mortality in immunocompromised patients. The aetiology of appendicitis is largely unknown but is thought to be multifactorial. Appendicitis is a suspected, but not well documented, complication from varicella zoster virus infection. Case Presentation. A five-year-old girl diagnosed with DiGeorge syndrome and a prolonged primary VZV infection was admitted due to abdominal pain, increasing diarrhoea, vomiting, and poor general condition. She developed perforated appendicitis and an intraperitoneal abscess. VZV DNA was detected by PCR in two samples from the appendix and pus from the abdomen, respectively. The child was treated with acyclovir and antibiotics and the abscess was drained twice. She was discharged two weeks after referral with no sequela. Conclusion. Abdominal pain in children with viral infections can be a challenge, and appendicitis has to be considered as a complication to acute viral diseases, especially if the child is immunocompromised.